Evaluation of the Impact of Compensation, Training Programs, and Job Placement on the Performance of Employees of the North Labuhanbatu Education Office - Anwar, Khairul; Andriani, Yulni; Mauliza, Yundi; Irawati, Irawati; Iskandar, Iskandar; Helmi, T.Ahmad (Journal of Finance and Business Digital, 2024)
Optimal employee performance is very important for the organization in achieving the goals that have been set. This study aims to evaluate the impact of compensation, job training, and job placement on employee performance at the North Labuhanbatu Regency Education Office. The research method used is a quantitative approach with a survey design, involving 100 respondents. The results of the analysis showed that all variables had a significant effect on employee performance, with job placement having the greatest influence (coefficient 0.410), followed by compensation (0.325) and job training (0.289). The significance test showed that all three variables simultaneously had a positive impact, with an R² value of 67.8%. These findings suggest the need for good management of all three factors to improve employee performance and the quality of education.